Integrated Marker-Based Watershed Segmentation with Hybrid median Filter - Kaur, Amanpreet; Verma, Ashish (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper focuses on marker based watershed segmentation algorithms. As marker based watershed segmentation algorithm causes over segmentation and cause noise in the image produced. So to reduce these problem different researchers has proposed different solutions, but the best solution is to use bilateral filter. The main objective of this paper is to find the gaps in existing literature. The different segmentation techniques are reviewed and found that marker based is best in most of cases because it marks the regions then segment them. But optimizing the marking regions is still an area of research.